- #1
r0bHadz
- 194
- 17
Homework Statement
p→(q→r)
¬q →¬p
p
-----------------------
∴r
Homework Equations
The Attempt at a Solution
My book gives the following solution:
(1) p - premise
(2) ¬q→¬p premise
(3) q, (1) and (2) and rule of detachment,
(4) p and q, law of conjuctive addition
.
.
.
Can anyone explain to me why you can use p on step 4?
Since in step 3, you are using step 1 and step 2, and p comes from step 1
Does the p not get "used" up? I don't understand why you're able to use it again.